Two new species of Clusia sect. Cordylandra (Clusiaceae) from the brejo de altitude vegetation, plateau of Ibiapaba, Ceará, Brazil - Alencar, Ana Cláudia; Nascimento-Jr, José Elvino Do; Bittrich, Volker; Farias-Castro, Antônio Sérgio; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2020)
Two new shrubby species of Clusia sect. Cordylandra are described and illustrated. The male flower of Clusia nogueirae presents an androecium forming a conical volcano-like synandrium around a well-developed pistillode covered with resin. The male flower of Clusia ibiapabensis, on the other hand, presents an androecium of free claviform stamens, forming a broad torus-like structure around a well-developed pistillode. The two species occur in regions of brejos de altitude in the plateou of Ibiapaba, Ceará state, northeastern Brazil.